Propaganda objectives and instruments as an element of foreign policy : case of Russian-Ukranian conflict - Diukova, Anfisa (2024)
A comparative qualitative analysis of propaganda as a tool of Russian and Ukrainian foreign policy was conducted, utilizing data gathered from February 24, 2022, to February 24, 2024. The objective of this study is to characterize the narratives employed by both nations within the sphere of war propaganda and to ascertain the methodologies each employs to influence public opinion. The thesis elucidates the specific imagery Russia and Ukraine seek to promulgate, the underlying rationales, and the instrumentalities they employ for such purposes.